PENGUJIAN TRANSFORMATOR DISTRIBUSI TIGA FASA - Novi Gusti Pahiyanti; Sigit Sukmajati (Sekolah Tinggi Teknik - PLN, 2016)
Media information which presents the technical data and specifications of the transformer is a nameplate, one of the data listed on the nameplate is the type of vector group transformer, vector group transformer which can inform you about the types of relationships winding on the transformer and the magnitude of the phase difference between the primary to the secondary. Vector group listed on the nameplate is particularly useful when the transformer will be operated in parallel, because the terms of parallel operation of transformers is to have the same type of vector group. Refers to the standard SPLN 50: 1987 and IEC 60076-1, vector Group of the routine work done to determine the type of relationship turns on the primary and secondary sections to match the nameplate. Methods to determine the type of vector group is done by connecting one of the terminals similar between the primary with the secondary, then the measured value of the voltage between the other terminal, the results of these measurements refer to the vector group testing formula and referring to the vector diagram measurement testing group.